METODA PERTAHAN DIRI PROGRAM VIRUS - Jufriadif Naam (LPPM STIKOM Dinamika Bangsa, 2013)
Virus is a computer program to duplicate or replicate by inserting copies of itself storage or document and to thenetwork secretly. Perform the functions of the Form Load, duplicate to the system, alter modify the registry anddamage the system. The results of the design of this virus can know how this virus works on the Windowsoperating system.